Abuse Is Abuse: The Influence of Type of Abuse, Victim Age, and Defendant Age on Juror Decision Making. Issue 1 (January 2021) - Sheahan, Chelsea L.; Pica, Emily; Pozzulo, Joanna D.
The purpose of the current study was to examine the role of victim age, defendant age, and type of abuse on mock juror decision making. Mock jurors ( N = 556) read a trial transcript in which a soccer coach was accused of sexual abuse or physical abuse against a player. The victim's age (child, adolescent, or young adult), the defendant's age (young, middle age, or older adult), and the type of abuse (sexual or physical) were varied. Mock jurors provided a dichotomous and continuous verdict and rated their perceptions of the victim and the defendant. Although no differences on mock jurors' dichotomous verdict were found due to victim age, defendant age, or type of abuse, mock jurors provided higher guilt ratings when the abuse was sexual and both the victim and defendant were described as young adults. Similarly, mock jurors rated the victim more positively when the victim was described as a young adult (vs. child) for both sexual and physical abuse cases, and rated the defendant more positively when the victim was described as a child compared with young adult in sexual abuse cases. These findings suggest that mock jurors were largely influenced by victim age, particularly when the victim was described as an adult compared with a child.